Borges y la lotería de los infortunios - Coaguila Valdivia, Jaime F. (2009)
The tale The Lottery in Babylon (1941) by the writer Jorge Luis Borges\nallows a reflection on the extent up to which chance is present in the Law, and\nwhether it is possible to create a theory of games in legal decisions that includes normative games, non-legal games and anomia games, everything backed by a playful reason as opposed to a strategic reason